2021
DOI: 10.1088/1741-4326/ac2875
|View full text |Cite
|
Sign up to set email alerts
|

Integrated model predictions on the impact of substrate damage on gas dynamics during ITER burning-plasma operations

Abstract: Divertor design and choice of plasma-facing materials (PFM) will be essential to the success of next-generation fusion reactors as they operate under more powerful scenarios. Understanding and controlling interactions between the plasma and PFM is essential to making these choices. Within these plasma–material interactions and especially in tungsten (W), the interplay between the most abundant plasma species (hydrogen isotopes and helium, He) with the wall material alters fuel retention. However, this interpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Results presented here also highlight the necessity of consistently modeling plasma conditions, electric fields and resulting E × B drifts inside and outside the sheath to accurately predict impurity transport and subsequent material erosion. Moreover, this work underlines the importance of a comprehensive sheath model in integrated modeling of impurity erosion, transport and redeposition [47] to account for the radial transport of low-Z impurities near divertor surface due to radial E × B drift in the sheath, and to accurately predict tungsten erosion, e.g. in ITER divertor.…”
Section: Discussionmentioning
confidence: 93%
“…Results presented here also highlight the necessity of consistently modeling plasma conditions, electric fields and resulting E × B drifts inside and outside the sheath to accurately predict impurity transport and subsequent material erosion. Moreover, this work underlines the importance of a comprehensive sheath model in integrated modeling of impurity erosion, transport and redeposition [47] to account for the radial transport of low-Z impurities near divertor surface due to radial E × B drift in the sheath, and to accurately predict tungsten erosion, e.g. in ITER divertor.…”
Section: Discussionmentioning
confidence: 93%
“…Figure 4(b) shows the integrated deuterium content over the thickness of the tungsten slab as a function of time in a similar way as helium in figure 4(a). The same general remarks can be made about the deuterium behavior as for helium, with the difference that the deuterium content is higher than the helium content mainly because of the differences in their respective implantation profiles: for helium implantation, the peak of the implantation profile is located at a depth of 1.6 nm below the surface, while the respective peak is at 2.2 nm below the surface for deuterium [23]. The times to reach 99% of the periodic steady state are estimated to be ∼10 300 s without accounting for the Soret effect and ∼4400 s with the Soret effect accounted for, which are longer than those in the helium case because of the higher overall content for deuterium.…”
Section: Deuteriummentioning
confidence: 79%
“…We found that, for all species examined, their total content over the depth of the tungsten slab simulated, after reaching their steady periodic state, was reduced (on average) by a factor of ∼3. While the actual value of the total content is strongly dependent on gas implantation and neutron irradiation conditions, especially on the location of the peak implantation profile [23], which would vary from one location to another in a divertor wall, the ratio of the species content between the cases with and without accounting for the Soret effect would be similar, under the assumption that transport of hydrogen isotopes is not heavily limited by self-clustering of helium and hydrogen binding to the resulting helium clusters. However, atomistic calculations have shown a strong propensity for helium self-clustering and overpressurized helium bubble formation, and a relatively strong trapping interaction of hydrogen with the helium clusters and bubbles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Lasa et al [140,141] reported an integrated model coupling the background plasma transport, the nearsurface sheath effects, the erosion and transport of wall materials across the scrape-off layer (SOF), sputtering and implantation of ions impacting on the material, and the dynamics of the subsurface gas atoms. The workflow of the model is shown in figure 13.…”
Section: Integrated Model For Plasma-materials Interactions Under Fus...mentioning
confidence: 99%